1996
DOI: 10.1017/s0004972700016798
|View full text |Cite
|
Sign up to set email alerts
|

On the Dunford-Pettis property in spaces of vector-valued bounded functions

Abstract: We show that £°°(ji, X) has the Dunford-Pettis property for some classical Banach spaces including L l (/i), C(K), the disc algebra A and H*".A Banach space X is said to have the Dunford-Pettis property if every weakly compact operator from X into an arbitrary Banach space is completely continuous, or equivalently, if given sequences (x n ) in X and (x^) in X*, both weakly convergent to zero, then (x^,x n ) tends to zero. A detailed exposition about this property can be found in [6]. In this reference, the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The sufficiency follows by [13] and [10]. In fact, in [13] it is shown that for finite measure space (Ω, µ), L ∞ (X) has the Dunford-Pettis property if and only if ∞ (X) has it.…”
Section: Corollarymentioning
confidence: 96%
See 2 more Smart Citations
“…The sufficiency follows by [13] and [10]. In fact, in [13] it is shown that for finite measure space (Ω, µ), L ∞ (X) has the Dunford-Pettis property if and only if ∞ (X) has it.…”
Section: Corollarymentioning
confidence: 96%
“…The sufficiency follows by [13] and [10]. In fact, in [13] it is shown that for finite measure space (Ω, µ), L ∞ (X) has the Dunford-Pettis property if and only if ∞ (X) has it. It is also proved in [13] that if either X is any L 1 -space or any L ∞ -space, then L ∞ (X) has the Dunford-Pettis property.…”
Section: Corollarymentioning
confidence: 96%
See 1 more Smart Citation